2005
DOI: 10.1016/j.jhsb.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Does the Absence of the Palmaris Longus Affect Grip and Pinch Strength?

Abstract: The palmaris longus tendon is the most frequently harvested tendon for reconstructive plastic and hand surgical procedures. A question patients often ask is whether loss of the palmaris longus will result in any functional deficit. In order to answer this question, the presence or absence of the palmaris longus muscle was clinically determined in 418 normal Asian subjects. All subjects also had their grip and pinch strengths measured. No statistically significant difference was seen in the grip or pinch streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 10 publications
3
58
0
Order By: Relevance
“…We have determined that grip strength of the hand wrist was not affected in the absence of PLM. It has been reported that patients requiring a palmaris longus tendon graft could be divided into two main groups depending on the functional status of the donor's upper extremity [11]. In the first group, the donor's upper extremity was normal and the palmaris longus was needed for reconstruction elsewhere, e.g., lip augmentation, ptosis correction, management of facial paralysis, tendon reconstruction in the opposite extremity, etc.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have determined that grip strength of the hand wrist was not affected in the absence of PLM. It has been reported that patients requiring a palmaris longus tendon graft could be divided into two main groups depending on the functional status of the donor's upper extremity [11]. In the first group, the donor's upper extremity was normal and the palmaris longus was needed for reconstruction elsewhere, e.g., lip augmentation, ptosis correction, management of facial paralysis, tendon reconstruction in the opposite extremity, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The probable effects of the palmaris longus muscle on hand functions have been studied and no clinically significant difference was observed [11]. We tried to answer the question of whether the functional value of the palmaris longus muscle bears a statistical value and significance in healthy subjects or not.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations